Producciones narrativas de la violencia política en Chile (1973 -- 2013): entre el ruido y el sonido...acecha el silencio. - SEPÚLVEDA GALEAS, MAURICIO; UBIERGO SICHEL, SEBASTIÁN (Nomadías)
Situated in the coordinates of post-structuralist thought, the text investigates the collective memory of political violence in Chile in the period 1973-2013 through field research using the method of productions. Using genealogical analytical tools applied to the study of governmentality, it rewrites an unfinished text that contained the results of previous research. The rewriting of the text is inserted during a plot of second and third order observations through which the ways of thinking about collective memory and its implications are problematized. The narrative productions are approached through an analysis that underlines the political rationalities, technologies of government, devices of political violence to analyze the generational continuities and differences that emerge in the period covered by the research.